2017
DOI: 10.1038/s41598-017-17376-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor prolyl-4-hydroxylase-1 is a convergent point in the reciprocal negative regulation of NF-κB and p53 signaling pathways

Abstract: Hypoxia-inducible factor 1α (HIF1α) induces the expression of several hundred genes in hypoxia aiming at restoration of oxygen homeostasis. HIF prolyl-4-hydroxylases (HIF-P4Hs) regulate the stability of HIF1α in an oxygen-dependent manner. Hypoxia is a common feature in inflammation and cancer and the HIF pathway is closely linked with the inflammatory NF-κB and tumor suppressor p53 pathways. Here we show that genetic inactivation or chemical inhibition of HIF-P4H-1 leads to downregulation of proinflammatory g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 74 publications
0
32
0
Order By: Relevance
“…Nevertheless, it is obvious that hydroxylation of p53 on P359 is only a part of the overall picture. Hydroxylases themselves mediate p53 activity, stability, and localization at multiple levels ( Deschoemaeker et al., 2015a , Janke et al., 2013 , Wang et al., 2014 , Xie et al., 2012 ), and recently the PHD1-dependent hydroxylation of p53 has been postulated ( Ullah et al., 2017 ). Such distributed controls are common in most signaling pathways, and it is emerging that the HIF pathway itself is regulated by hydroxylation at multiple levels.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is obvious that hydroxylation of p53 on P359 is only a part of the overall picture. Hydroxylases themselves mediate p53 activity, stability, and localization at multiple levels ( Deschoemaeker et al., 2015a , Janke et al., 2013 , Wang et al., 2014 , Xie et al., 2012 ), and recently the PHD1-dependent hydroxylation of p53 has been postulated ( Ullah et al., 2017 ). Such distributed controls are common in most signaling pathways, and it is emerging that the HIF pathway itself is regulated by hydroxylation at multiple levels.…”
Section: Discussionmentioning
confidence: 99%
“…HIF prolyl-4-hydroxylases (HIF-P4H) inhibition exerts a positive influence on the activation and stability of the tumor suppressor p53, which besides positively regulating the expression of pro-apoptotic genes and the activity of the caspases, is known to be a negative regulator of inflammation [ 40 , 41 ]. Ullah et al showed that the same pathway, negatively regulating the inflammatory response in vitro and in vivo, contributes to the suppression of NFκB activity [ 42 ]. The pro-inflammatory role of hypoxia is also due to the direct activation of the NFκB pathway.…”
Section: Dual Role Of Hypoxia In Inflammation and Immune System Rementioning
confidence: 99%
“…Subsequent studies have supported alterations in hydroxylase-dependent signaling with changes in NF-κB activity [21,49,87,88,89,90,91]. The strongest direct evidence for hydroxylation of IKKβ was provided by Zheng and colleagues [47].…”
Section: Evidence For Non-hif Hydroxylation Targetsmentioning
confidence: 99%
“…More recently, co-immunoprecipitation studies confirmed that PHD1 interacts with p53. In addition, tandem mass spectrometry (MS/MS) revealed that PHD1 most probably hydroxylates p53 at proline 142 [49]. Subsequent experiments using cells expressing a proline to alanine mutation at the residue 142 (Pro142Ala) within the mutated p53 gene were performed [49].…”
Section: Evidence For Non-hif Hydroxylation Targetsmentioning
confidence: 99%
See 1 more Smart Citation